Pengaruh Kepemimpinan Transformasional, Job Insecurity, dan Locus Of Control terhadap Turnover Intention dengan Human Relation sebagai Variabel Moderating - Anang Ma'ruf; Nunik Kusnilawati; Albert Albert (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research analyzes the influence of transformational leadership, job insecurity, and locus of control on turnover intention and how human relations moderate transformational leadership, job insecurity, and locus of control on turnover. This type of research is quantitative using the Moderated Regression Analysis (MRA) test as data analysis. The research results show that transformational leadership, job insecurity, and locus of control influence turnover intention, and human relations can play a moderating role on the variables of transformational leadership, job insecurity, and locus of control on turnover intention. In conclusion, transformational leadership, job insecurity, and locus of control influence turnover intention. It is hoped that the results of this research can be a reference for companies in formulating policies that focus on minimizing employee turnover through strategic managerial and human resource approaches. Keywords: Job Insecurity, Transformational Leadership, Locus of Control, Turnover Intention, Human Relations